ATG12 deficiency leads to tumor cell oncosis owing to diminished mitochondrial biogenesis and reduced cellular bioenergetics - Liu, He; He, Zhaoyue; Germič, Nina; Ademi, Hyrijie; Frangež, Živa; Felser, Andrea; Peng, Shuang; Riether, Carsten; Djonov, Valentin; Nuoffer, Jean-Marc; Bovet, Cédric; Mlinarič-Raščan, Irena; et al. (Cell death and differentiation, 2020)
In contrast to the "Warburg effect" or aerobic glycolysis earlier generalized as a phenomenon in cancer cells, more and more recent evidence indicates that functional mitochondria are pivotal for ensuring the energy supply of cancer cells. Here, we report that cancer cells with reduced autophagy-related protein 12 (ATG12) expression undergo an oncotic cell death, a phenotype distinct from that seen in ATG5-deficient cells described before. In addition, using untargeted metabolomics with ATG12-deficient cancer cells, we observed a global reduction in cellular bioenergetic pathways, such as β-oxidation (FAO), glycolysis, and tricarboxylic acid cycle activity, as well as a decrease in mitochondrial respiration as monitored with Seahorse experiments. Analyzing the biogenesis of mitochondria by quantifying mitochondrial DNA content together with several mitochondrion-localizing proteins indicated a reduction in mitochondrial biogenesis in ATG12-deficient cancer cells, which also showed reduced hexokinase II expression and the upregulation of uncoupling protein 2. ATG12, which we observed in normal cells to be partially localized in mitochondria, is upregulated in multiple types of solid tumors in comparison with normal tissues. Strikingly, mouse xenografts of ATG12-deficient cells grew significantly slower as compared with vector control cells. Collectively, our work has revealed a previously unreported role for ATG12 in regulating mitochondrial biogenesis and cellular energy metabolism and points up an essential role for mitochondria as a failsafe mechanism in the growth and survival of glycolysis-dependent cancer cells. Inducing oncosis by imposing an ATG12 deficiency in solid tumors might represent an anticancer therapy preferable to conventional caspase-dependent apoptosis that often leads to undesirable consequences, such as incomplete cancer cell killing and a silencing of the host immune system.